ANALISIS STRATEGI HUMAS PDAM KOTA TERNATE DALAM PENANGANAN KELUHAN DAN KOMPLAIN WARGA KECAMATAN KOTA TERNATE UTARA DAN KOTATERNATE TENGAH TERHADAP DAMPAK EKSPLOITASI SUMBER MATA AIR AKE GAALE - Dewi, Mutia; Djalaluddin, Laily Wahyuni (Universitas Negeri Yogyakarta, 2016)
Based on the results of research, Public Relations of water supply company Ternate city in complain handling Ake Gaale water source, they perform of internal an external function. Public Relations of water supply company Ternate city excecutes four important steps started fact finding and defining the problem, planning and programming, action and communication, and evaluation. In the evaluation step, Public Relation of water supply company Ternate city found that each of the programs was not effectively done. Alternative step taken by Public relation was engaging the Government of Ternate to be involved in the follow-up meeting about problems at Ake Gaale water source, as well as the presence by Government of Ternate also intended to be a mediator in the mediation process between water supply company Ternate city and residents of Sangaji that failed to build their communication each other.